2002
DOI: 10.2298/avb0201043n
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis in dogs and cats in the Belgrade area

Abstract: Giardia infection is an ongoing problem in Serbia, since 8,0% of the children in the Belgrade area are infected. In the light of the zoonotic potential of Giardia infection, a total of 248 companion animals (167 dogs and 81 cats) were examined for giardiasis in the same urban area. The overall rates of infection in dogs and cats were 14.4% (24/167) and 22.2 % (18/81), respectively. Significantly (p<0.05, p<0.01) higher infection rates were found in stray (18.7%) and farm (36.4%) dogs than in household pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A 2015 study in shelter dogs, however, showed a remarkably higher prevalence of infections with Giardia of 65.67% (88/134; 95% CI: 57.33–73.34) belonging to the assemblages C and D [111]. In 2001, a study found a higher Giardia prevalence in kittens (7/23; 30.43%, 95% CI: 14.39–51.14) than in adult pet cats (11/58; 18.96%, 95% CI: 10.40–30.57), however all 95% CIs overlapped [112]. Other data from 2012 seemed to indicate a decrease in the Giardia infection rate in cats [113].…”
Section: Resultsmentioning
confidence: 99%
“…A 2015 study in shelter dogs, however, showed a remarkably higher prevalence of infections with Giardia of 65.67% (88/134; 95% CI: 57.33–73.34) belonging to the assemblages C and D [111]. In 2001, a study found a higher Giardia prevalence in kittens (7/23; 30.43%, 95% CI: 14.39–51.14) than in adult pet cats (11/58; 18.96%, 95% CI: 10.40–30.57), however all 95% CIs overlapped [112]. Other data from 2012 seemed to indicate a decrease in the Giardia infection rate in cats [113].…”
Section: Resultsmentioning
confidence: 99%
“…differences. These may be due to geographical variation or to differences in the number of animals and type of population surveyed, or may be attributed to different rates of sensitivities of diagnostic procedure used (10,14). Although the prevalence in male dogs (12.24%) is slightly higher than that of female dogs (11.76%), there were no significant gender differences.…”
Section: Discussionmentioning
confidence: 94%